Injury pattern in Icelandic elite male handball players - Rafnsson, E. T.; Valdimarsson, Ö.; Sveinsson, T.; Árnason, Á. (Clinical Journal of Sport Medicine, 2019)
Objective: To examine the incidence, type, location, and severity of injuries in Icelandic elite male handball players and compare across factors like physical characteristics and playing position.Design: Prospective cohort study.